Climate change and Chinese farmers: Perceptions and determinants of adaptive strategies - Shi-yan ZHAI; Gen-xin SONG; Yao-chen QIN; Xin-yue YE; Mark Leipnik (Journal of Integrative Agriculture, 2018)
Farmers’ perceptions, beliefs, adaptive strategies, and barriers regarding climate change are critical to promoting sustainable ecosystems and societal stability. This paper is based on an extensive survey of 1 500 farmers and their households in Henan Province in China during 2013–2014. Henan is the largest agricultural province in China with over 51 million farmers. The survey results showed that approximately 57% of the respondents perceived the direct impact of climate change during the past 10 years, with 70.3% believing that climate change posed a risk to their livelihood. Not surprisingly, most farmers reported that they have adopted new measures to mitigate the negative impacts of climate change. The main barriers hindering farmers’ adopting adaptation measures were lack of funds and timely information. A multinomial logit model revealed that land ownership, knowledge of crop variety and the causes of climate change, as well as the belief of climate change, were all positively related to the likelihood of employing adaptive strategies. Moreover, the percentage of households engaging in agriculture activity, and years of engaging in farming were both negatively correlated with famer's likelihood of adopting adaptation strategies. More importantly, farmers with high incomes were less likely to adopt adaptive strategies and more willing to engage in other business activities. In conclusion, it is important to communicate climate change related information and government policies in rural areas, promote farmer associations and other educational outreach efforts to assist Chinese farmers to deal with climate change.